MODERATING EFFECT OF ABNORMAL AUDIT FEES ON THE RELATIONSHIP BETWEEN AUDIT DELAY AND THE QUALITY OF FINANCIAL REPORTING: A STUDY OF LISTED INDUSTRIAL GOODS FIRMS IN NIGERIA - Ogunmodede, E. O.; Aggreh, M.; Nwokediba, E. E.; Udeh, F. N.; Aggreh, M. (Journal of Global Accounting, 2023)
The study investigated the moderating effect of abnormal audit fees on the relationship between audit delay and the quality of financial reporting in firms. The specific objective of the study were to determine the effect of audit report time lag and abnormal audit fees on accruals quality of listed industrial goods in Nigeria. The study also examined whether abnormal audit fees affect the relationship between audit report time lag and accruals quality of listed industrial goods in Nigeria. The study population was made up of thirteen (13) industrial goods that were listed on the Nigerian Exchange group. Purposive sampling method was used to select the seven (7) firms that made up the sample participants. Secondary data were obtained from the annual financial reports of the selected industrial goods for a 10-year period spanning 2012-2021, using 2012 as base year for accrual quality estimation. Moderated Ordinary Least Square regression analysis was utilized in testing all the hypotheses of the study. The findings revealed the following: audit report time lag has no significant effect on the accruals quality of listed industrial goods in Nigeria (p-value = 0.7970); abnormal audit fee has no significant effect on the accruals quality of listed industrial goods in Nigeria (p-value = 0.8174); there is no moderating effect of abnormal audit fees on the relationship between audit report time lag and accruals quality of listed industrial goods in Nigeria (p-value = 0.4970). In conclusion, abnormal audit fees do not have the potential to indicate higher audit risks, which can prompt the external auditor to pay closer attention to details, ultimately leading to improved financial reporting quality. It was recommended that companies should strive to maintain efficient audit processes and timely submission of financial statements to external auditors to ensure that any potential issues can be identified and resolved promptly